Anatomical Responses of Rice (Oryza Sativa L.) to Aluminium Toxicity (Journal of Bangladesh Academy of Sciences, 2020)
Anatomical response of rice (Oryza sativa L.) to aluminium toxicity grown in sand culture and half strength Hoagland solution revealed that aluminium stress caused a decrease in diameter of the root and the shoot. Aluminium toxicity reduced the number of metaxylem vessels in the root of rice. Number of sclerenchyma cells was more in aluminium-treated rice root. Under Al stress, smaller sized vascular bundles were found in the leaf of rice. Size and frequency of bulliform cells were increased in the leaf of Al-treated plants than that in control plants. Al treatment caused closure of stomata in rice leaves.Journal of Bangladesh Academy of Sciences, Vol. 43, No. 2, 123-131, 2019